Balloon Angioplasty in the Treatment of Children with Native Aortic Coarctation: Is Reintervention Predictable? - Yaseen, Munaf Jarallah; Akram, Nabeeha Najatee; Abdulridha, Yasir Ibrahim (Scripta Medica, 2025)
Background/Aim: Reintervention after balloon angioplasty is often considered inevitable in children with coarctation of the aorta (COA). The present study aimed to evaluate predictors of re-intervention after balloon angioplasty for coarctation of the aorta, with the goal of identifying patient and procedural characteristics that may influence long-term outcomes.Methods: A retrospective study involved children who underwent balloon angioplasty for coarctation of the aorta at a specialised interventional cardiovascular centre over a period of four years. A two set of data were collected: first, the clinical-demographical data (age, sex, weight, associated congenital heart disease, syndromic features). Second, a procedure related data (type of anaesthesia, heparin use, type and number of balloons used, fluoroscopy duration, procedure outcome and complications). Early interventional success is considered if the peak systolic pressure gradient (PG) achieves less than 20 mm Hg. All patients were followed for 12 months during which the pressure gradient was measured periodically by echocardiography and any reintervention was documented. Results: A total of 37 children underwent balloon angioplasty during the study period. Most children (62.2 %) underwent the procedure after the first year of life. The procedure was successful early in 35 (95 %) of cases. On follow-up for 12 months, 8 patients (22 %) needed re-intervention. Eight factors were identified as significantly associated with the likelihood of re-intervention, including younger age, lower ejection fraction, use of two balloons, procedural complications, longer duration, smaller COA size, higher residual pressure gradient and a lower reduction in the peak systolic PG.Conclusion: This study emphasised the multifactorial nature of re-intervention risk following balloon angioplasty for COA. Careful consideration of patient age, ventricular function, anatomical characteristics, procedural complexity and immediate haemodynamic results is essential to decrease the need for reintervention.
Keywords: Angioplasty, balloon, coronary; Aortic coarctation; Child; Infant; Coronary restenosis